2013
DOI: 10.1007/s00709-013-0484-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of antioxidant machinery in α-tocopherol-enriched transgenic Brassica juncea plants tolerant to abiotic stress conditions

Abstract: The antioxidant machinery in plants consists of several components with unique or overlapping functions that combat the deleterious production of reactive oxygen species (ROS) induced by stress conditions. Tocopherols are a group of powerful antioxidants having additional roles in signaling and gene expression, with α-tocopherol being the most potent form. In the present study, we used wild-type (WT) and α-tocopherol-enriched transgenic (TR) Brassica juncea plants grown under salt, heavy metal, and osmotic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(50 citation statements)
references
References 36 publications
2
48
0
Order By: Relevance
“…Reduction of ROS level is a major biotechnology strategy used to protect plants from various abiotic stresses [3840]. In the study reported herein, ROS produced by C. reinhardtii cause oxidative damage, which results in cell death under heat treatment at 42 °C for 40 min.…”
Section: Discussionmentioning
confidence: 95%
“…Reduction of ROS level is a major biotechnology strategy used to protect plants from various abiotic stresses [3840]. In the study reported herein, ROS produced by C. reinhardtii cause oxidative damage, which results in cell death under heat treatment at 42 °C for 40 min.…”
Section: Discussionmentioning
confidence: 95%
“…For example, overexpression of the γ-tocopherol methyl transferase gene from A. thaliana in transgenic Brassica juncea plants resulted in an over sixfold increase in the level of α-toc, induced by a variety of abiotic stresses (Yusuf and Sarin 2007). Moreover, α-toc-enriched transgenic B. juncea was found to increase the tocopherol levels which enhanced its tolerance against Cd-induced stress (Kumar et al 2013). Also, some other transgenic plants, such as potato, with the reduced expression of some other proteins, e.g., manganese stabilizing protein, an important component of the PSII, were found to accumulate α-toc and other antioxidants as a consequence of Zn treatment (Gururani et al 2013).…”
Section: Tocopherols and Tocotrienolsmentioning
confidence: 95%
“…The staining procedure followed was a modification of that used for plant leaves (Kumar et al 2013). Three-dayold nitrogen-fixing and nitrogen-supplemented cultures of recombinant Anabaena strains, AnpAM and AnsodA + were inoculated in the corresponding fresh growth medium at 1 µg chlorophyll a density mL −1 in the absence or presence of 0.2 µM methyl viologen.…”
Section: Detection Of Superoxide Anion Radical Using Nitroblue Tetrazmentioning
confidence: 99%